PELAKSANAAN PENGAWASAN WARGA NEGARA ASING DI WILAYAH KERJA KANTOR IMIGRASI KELAS II BELAWAN BERDASARKAN UU NO. 6 TAHUN 2011 TENTANG KEIMIGRASIAN - Warhan Wirasto; Suhaidi Suhaidi; Mahmul Siregar; Jelly Leviza (USU LAW JOURNAL, 2016)
ABSTRACT Immigration based on article 1 Act number 6 year 2011 is a case history of traffic or people coming out of Indonesia’s territory and surveillance in order to preserve the enforcement of state sovereignty. Immigration have 3 function or in common named “ Tri Function of Immigrastion”, that is community service function, law enforcement function and economic fasilitator function. Indonesian layout area especially Belawan has a strategic location from geografic or trading because close to Singapore and make a lot of factory build in this region so that things have a correlation with the user of skilled people that comes from another country and make a lot of foreign people from another country want to enter and come to Indonesia, which is that foreigner has a goal and different purpose. Immigration policy for that foreigner in 2 (two) approach that is prosperity approach, which is only foreigner that bring benefit for prosperity and wallfare to Indonesian people allowed to entering Indonesia. And then security approach that is give Immigration permit to them that not harm  security of country and general order. The problems that faced for surveillance of foreigner system based on Act Number 6 year 2011 in Indonesia teritory especially in Immigration office of class II Belawan region and what that Immigration office of class II Belawan do to foreigner that breaking Immigration rule. The research Methods that used is the juridical normative that is study in konsepsional order from the meaning and the intent from regulation national law that have a correlation with Immigration surveillance and action to the permit of the foreigner who has stay in indonesia and empirical juridical that is seeing the fact that occur in the field, and then connect to regulations now. The setting of surveillance for foreigner in Indonesia have been set up in Immigration act number 6 year 2011 but now the applications in the field esspecially in Imigration class II office of Belawan region have a few barrier and obstacles.   Keywords : Supervision, Foreigner, Immigration office of Belawan